2022
DOI: 10.21831/jitp.v9i2.47095
|View full text |Cite
|
Sign up to set email alerts
|

Flipgrid: Video-based applications to improve English ability for junior high school students

Abstract: globalisasi. Selain itu, bahasa inggris merupakan bahasa yang dibutuhkan dalam level international. Sehingga, penelitian ini bertujuan untuk menguji pengaruh Flipgrid dengan fitur utama berbasis video terhadap kemampuan bahasa inggris siswa Sekolah Menengah Pertama. Metode eksperimen dengan pendekatan kuantitaif yang digunakan dalam penelitian ini. Desain yang digunakan yaitu pre-experiment dengan satu grup pre-test dan post-test. Instrumen yang digunakan untuk pengumpulan data adalah tes bahasa inggris, yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A study by N.R. Putri et al (2022) focuses on investigating the impact of the "Flipgrid" video app on younger pupils. The results of the study showed that digital and information technologies have a positive impact on the development of interactive tasks aimed at increasing the level of communicative competence.…”
Section: Discussionmentioning
confidence: 99%
“…A study by N.R. Putri et al (2022) focuses on investigating the impact of the "Flipgrid" video app on younger pupils. The results of the study showed that digital and information technologies have a positive impact on the development of interactive tasks aimed at increasing the level of communicative competence.…”
Section: Discussionmentioning
confidence: 99%